Pollen Morphology Variation of Undergrowth Plants in Bantarbolang Nature Reserve, Pemalang, Central Java - Anisatul Khabibah Zaen; Sukarsa Sukarsa; Siti Samiyarsih (Fakultas Biologi Universitas Jenderal Soedirman, 2019)
Undergrowth is ground cover plant which is generally in the form of herbs, grass or low shrubs. Mostly undergrowth is flowering plants. The Flower is part of plant for generative reproduction that consists of several organs that consist of pedicellus, receptacullum, perianthium, pistillum and stamen that contain pollen. Pollen is part of the flower that functions as a generative reproduction agent because it contains male gamete. Pollen has a distinctive character in each plant so that it can be used as a tool for identifying plants. Sampling location was conducted in Bantarbolang Nature Reserve, a conservation area located in Kebon Gede Village, Bantarbolang District, Pemalang Regency. The objective of research is to know the morphological character of undergrowth pollen in the Bantarbolang Nature Reserve. The research used a survey method with explorative sampling techniques. The variables that observed are the morphological character of pollen with the parameters consist of pollen unit, shape, aperture, diameter, and ornamentation. Sample preparation uses the acetolysis method and descriptive data analysis. Based on the results of the research found 6 species of undergrowth with different pollen morphological characters in the pollen shape (sub-speroidal and prolate), aperture (tricolpate, tricolporate and fenestrate) and ornamentation type (psilate, reticulate, perforate and echinate). The pollen units of all species have the same type, monad